IoT Enabled Intelligent Tracking System for Forest and Hilly Region - M., Ruban Gladwin; N., Kasthuri; P., Jenifer; D., John Jebastin; M., Muthu Krishnan; K., Kaliarasan (Journal of ISMAC, 2026)
Wireless communication networks in mountain and forest regions face serious degradation due to specific problems like attenuation, shadowing, and multipath fading because of dense trees and hilly topographic conditions. Traditional satellite communication assists in overcoming these disadvantages, but it remains costlier and power-intensive, and hence not suitable for remote IoT applications. This paper presents an IoT-based smart tracking system using LoRa (Long Range) communication technology, which serves as a cost-effective, energy-efficient, and long-range communication solution to overcome these specific drawbacks. The IoT-based tracking system utilizes GPS, a heart sensor, and an accelerometer, along with ESP32 and LoRa communication modules, to measure and implement self-communication without cellular services. The experimental analysis confirms that the designed LoRa-based network enables reliable connectivity with low power consumption and an extended range. This work establishes an effective and scientific basis for real-time surveillance, alert messages, and environmental monitoring in forest and hill regions.
Keywords: LoRa; Mesh Networks; Wide Area Tracking; Long Range Tracking; Internet of Things